Pengaruh Motivasi Belajar dan Persepsi Harapan Orang Tua terhadap Optimisme Penyelesaian Skripsi Mahasiswa - Kurniawan, Yayak; Desiyanto, Jatim (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
The process of completing a thesis often presents significant challenges for final-year students, requiring them to sustain a high level of optimism to overcome academic and psychological obstacles. Internal factors, such as learning motivation, and external influences, particularly parental expectations, play an essential role in supporting students’ perseverance throughout this process. This study aims to examine the influence of learning motivation and parental expectations on the optimism of final-year students in completing their thesis. Using a quantitative approach, the research involved 35 final-year students of STKIP PGRI Sampang, selected through purposive sampling. Data were collected using questionnaires and analyzed with SPSS software. The results of the F-test indicated a simultaneous influence of learning motivation and parental expectations on students’ optimism in completing their thesis, with a significance value of 0.000 < 0.05. Partial tests further revealed that learning motivation (sig. 0.034 < 0.05) and parental expectations (sig. 0.032 < 0.05) each significantly contributed to students’ optimism. These findings highlight that both individual effort and family support are critical in strengthening students’ positive outlook during the thesis completion process. The study contributes to the understanding of psychological and social factors affecting student success and offers practical insights for educators and parents in fostering supportive learning environments.